2011
DOI: 10.4064/aa146-1-5
|View full text |Cite
|
Sign up to set email alerts
|

An orthogonal test of the L-functions Ratios Conjecture, II

Abstract: ABSTRACT. We test the predictions of the L-functions Ratios Conjecture for the family of cuspidal newforms of weight k and level N , with either k fixed and N → ∞ through the primes or N = 1 and k → ∞. We study the main and lower order terms in the 1-level density. We provide evidence for the Ratios Conjecture by computing and confirming its predictions up to a power savings in the family's cardinality, at least for test functions whose Fourier transforms are supported in (−2, 2). We do this both for the weigh… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 45 publications
0
9
0
Order By: Relevance
“…70 Another problem is that the main term in the 1-level density agrees with random matrix theory, but the arithmetic of the family does not surface until we examine the lower order terms (which control the rate of convergence; see for example [103,107,133]). One promising line of research is the L-functions Ratios Conjecture [116,117], which is supported by corresponding calculations for random matrix ensembles (see [118,122,[125][126][127]131] for some recent work supporting these conjectures, especially [118] for a very accessible introduction to the method and a summary of its successes). Another approach is through hybrid product formulas [123].…”
Section: Future Avenuesmentioning
confidence: 98%
“…70 Another problem is that the main term in the 1-level density agrees with random matrix theory, but the arithmetic of the family does not surface until we examine the lower order terms (which control the rate of convergence; see for example [103,107,133]). One promising line of research is the L-functions Ratios Conjecture [116,117], which is supported by corresponding calculations for random matrix ensembles (see [118,122,[125][126][127]131] for some recent work supporting these conjectures, especially [118] for a very accessible introduction to the method and a summary of its successes). Another approach is through hybrid product formulas [123].…”
Section: Future Avenuesmentioning
confidence: 98%
“…(2-3) (In the current paper, the parameter Q plays the role of jᏲ N j.) Asymptotic formulas for R Ᏺ N .˛; / have been conjectured for a variety of families Ᏺ N (see Conrey and Snaith 2007;Goes et al 2010;Huynh et al 2011;Miller 2008;2009b;Miller and Montague 2011]) and are believed to hold up to errors of size jᏲ N j 1=2C for any > 0. The evidence for the correctness of this error term is limited to test functions with small support (frequently significantly less than .…”
Section: Background and New Resultsmentioning
confidence: 99%
“…The powerful ratios conjecture of Conrey, Farmer and Zirnbauer Conrey et al 2005b] yields a formula for D 1IQ=2;Q .Á/, which is believed to hold up to an error of O .Q 1=2C /. While there have been several papers [Conrey and Snaith 2007;David et al 2013;Goes et al 2010;Huynh et al 2011;Miller 2008;2009b;Miller and Montague 2011] showing agreement between various statistics involving L-functions and the ratios conjecture's predictions, evidence for this precise exponent in the error term is limited; the reason this exponent was chosen is the "philosophy of square root cancellation". While some of the families studied have 1-level densities that agree beyond square root cancellation, it is always for small support (supp.y Á/ .…”
Section: Introductionmentioning
confidence: 99%
“…One may weaken the Ratios Conjecture by not discarding these terms; this is done in [Mil5,MilMo], where as predicted it is found that these terms do not contribute. To provide a better test, we also do not drop these terms (see Remark 2.1 for a discussion of which terms, for this family, may be ignored).…”
Section: Recipementioning
confidence: 93%
“…These have been verified as accurate (up to square-root agreement as predicted!) for suitably restricted test functions for orthogonal families of cusp forms [Mil5,MilMo] and the symplectic families of Dirichlet characters [Mil3,St] and elliptic curves twisted by quadratic characters [HuyMil]. Further, these lower order terms have been used as inputs in other problems, such as modeling the first zero above the central point for certain families of elliptic curves [DHKMS].…”
Section: Introductionmentioning
confidence: 99%